2021
DOI: 10.1172/jci.insight.143285
|View full text |Cite
|
Sign up to set email alerts
|

VEGFA165 gene therapy ameliorates blood-labyrinth barrier breakdown and hearing loss

Abstract: Millions of people are affected by hearing loss. Hearing loss is frequently caused by noise or aging, and often associated with loss of pericytes. Pericytes populate small vessels in the adult cochlea. However, their role in different types of hearing loss is largely unknown. Using an inducible and conditional pericyte depletion mouse model and noise-exposed mouse model, we show that loss of pericytes leads to marked changes in vascular structure, leading, in turn, to vascular degeneration and hearing loss. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 67 publications
3
27
0
Order By: Relevance
“…3A , we found the control mice showed no significant hearing threshold change after DT injection. In contrast, the hearing threshold in pericyte-depleted animals was significantly elevated at 1 week after DT injection and persisted to two weeks after DT injection (n=10, P<0.0001, two-way ANOVA), consistent with our previous observation (Zhang et al, 2021).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…3A , we found the control mice showed no significant hearing threshold change after DT injection. In contrast, the hearing threshold in pericyte-depleted animals was significantly elevated at 1 week after DT injection and persisted to two weeks after DT injection (n=10, P<0.0001, two-way ANOVA), consistent with our previous observation (Zhang et al, 2021).…”
Section: Resultssupporting
confidence: 91%
“…To investigate whether pericyte loss affects vascular stability in the spiral ganglion in adult mice, we created an inducible pericyte depletion mouse model ( Pdgfrb CreERT+/- ; R26 iDTR+/- ) by crossing Pdgfrb CreERT2+/- transgenic mice with ROSA26 iDTR+/+ mice, an inducible daiphtheria toxin receptor (iDTR) mouse line carrying Cre-dependent simian DTR, which leads to cell death with the administration of the diphtheria toxin (DT) (Buch et al, 2005; Zhang et al, 2021) (as illustrated in Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the cochlea, pericytes contribute to angiogenesis (the formation of new blood vessels), vascular integrity, and blood flow control (Reviewed in Caporarello et al, 2019). Pericyte depletion (in a Cre-mediated diphtheria toxin inducible mouse model) causes reduced vascular density, variable vessel size, vascular leakage, and hearing loss (Zhang J et al, 2021). Notably, RTqPCR and immunohistochemical analysis indicated that vascular endothelial growth factor isoform A165 (VEGFA165) is particularly important for pericyte function.…”
Section: The Role Of Pericytes In the Blood-labyrinth Barriermentioning
confidence: 99%
“…Another important function of the SV is to regulate the secretion of the endolymph and maintain cochlear homeostasis (Taukulis et al, 2021;Zhang et al, 2021). Among these, H(+) -ATPase (ATP6V1B1 and ATPV0A4) and bicarbonate/chloride transporter SLC26A4 (Pendrin) are expressed in the SV, and regulate the secretion of H+ and HCO3− in the endolymph to maintain pH homeostasis (Mittal et al, 2017); similarly, the Ca(2+) -ATPase and Ca(2+) channels expressed in the SV jointly maintain Ca(2+) homeostasis in the endolymph (Nin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%